2018
DOI: 10.15547/bjvm.1045
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Linguatula serrata nymphs and pathological lesions of infected mesenteric lymph nodes among ruminants in Kermanshah, western Iran

Abstract: Linguatulosis is one of the important zoonotic diseases that cause public health problems worldwide. This study was carried out from March 2014 to February 2015 to estimate the prevalence of nymphal stages of Linguatula serrata in ruminants of different sex and age slaughtered at the Kermanshah municipal abattoir, in western Iran. For this purpose, the mesenteric lymph nodes (MLNs) were examined grossly and three MLNs for each animal were collected for parasitological and pathological studies. Of the total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…A plethora of studies carried out either in Iran or other parts of the world confirmed the impact of aging on increased rate of infection with Linguatula serrata parasite in sheep and other livestock (Fard et al, 2012;Kheirabadi et al, 2015;Nematollahi et al, 2015;Hashemnia et al, 2016). In this study, rate of the infection in sheep over 19 months of age was higher than that in younger ones.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A plethora of studies carried out either in Iran or other parts of the world confirmed the impact of aging on increased rate of infection with Linguatula serrata parasite in sheep and other livestock (Fard et al, 2012;Kheirabadi et al, 2015;Nematollahi et al, 2015;Hashemnia et al, 2016). In this study, rate of the infection in sheep over 19 months of age was higher than that in younger ones.…”
Section: Discussionsupporting
confidence: 71%
“…It should be noted that in this research, mesenteric lymph nodes of the sheep were examined because it is the first site that the parasite chooses to enter (Shekarforush & Arzani-Shahni, 2002). However, based on other conducted studies in Iran, the reported infection rates of sheep mesenteric lymph nodes in various parts of Iran were as followed: Isfahan, 11% (Kheirabadi et al, 2015); Urmia, 65.7% (Yakhchali et al, 2009); Shiraz, 11.5% (Shekarforoush et al, 2004); Tabriz, 52.5% (Tavassoli et al, 2007) Kermanshah, 19.7% (Hashemnia et al, 2016). In this research, the infection rate of sheep in their mesenteric lymph nodes was 8.6%.…”
Section: Discussionmentioning
confidence: 50%